Improving students understanding on fluid dynamics through IBL-STEM model with formative assessment - Parno, Parno (2021)
Fluid dynamics is related to science and technology in everyday's life, but students still have low understanding about it. This research aims to correct the understanding and describe students' difficulties on the topic of fluid dynamics after Inquiry-Based Learning integrated STEM with Formative Assessment. This mixed methods with an embedded experimental design made use of research subject of 34 students (M=14 and F=20) of grade XI in a high school at Jombang, Indonesia, which were selected with purposive sampling. The research instrument used was the fluid dynamics understanding test instrument in the form of reasoned multiple-choice questions with a reliability of 0.774. The data analysis was done with Wilcoxon Signed-Rank test, N-gain, d-effect, and and the analysis of the description of students' answer. The result of the study shows that the learning process was able to significantly improve students' conceptual understanding with the N-gain value of 0.628 (medium category) and d-effect size of 3.645 (very large category). After the learning process, students still have great difficulty in learning two things, which are flow rate with constant magnitude and the relation between pressure, surface area of the space, and the flow speed. Other than that, students still feel some difficulty to analyze (1) the relation between speed of flow and radius of space, (2) the construction of the proof of constant debut, (3) aerodynamic lift of two wings of an aeroplane, and (4) the phenomena of someone standing near a moving train, and (5) the relation between the height of water reservoir and the flow rate.